Long-term monitoring of Azorean forest arthropods - Borges, Paulo A. V. (2022)
Since 2012 we are conducting in Azorean Islands (Portugal) native and exotic forests a long-term monitoring study named SLAM - Long Term Ecological Study of the Impacts of Climate Change in the natural forest of Azores. This long-term monitoring study is monitoring arthropods (Arthropoda), aiming to understand the impact of biodiversity erosion drivers in Azorean native forests arthropod distribution, abundance and diversity. The current dataset represents arthropods that were recorded using a total of 42 passive SLAM traps (Sea, Land and Air Malaise) deployed inside native and exotic forest fragments in seven Azorean Islands (Flores, Faial, Pico, Graciosa, Terceira São Miguel and Santa Maria). This manuscript is the fifth data-paper contribution based on data from this long-term project. We provide data of terrestrial arthropods belonging to Arachnida (excluding Acari), Diplopoda, Chilopoda and Insecta classes (excluding Collembola, Diptera, Hymenoptera and Lepidoptera) from seven Azorean Islands during the 2012-2021 period. Data from spiders (Araneae) from the Pico and Terceira Islands is not included in this publication since this data was already published elsewhere (Costa and Borges 2021; Lhoumeau et al. 2022). We collected a total of 176007 specimens, of which 168565 (95.7%) were identified at species or subspecies level. Among these identified specimens, 106 350 (62%) were adults. For Araneae and some Hemiptera species, juveniles are also included in the data presented in this paper, since the low diversity in the Azores allows a relatively precise species-level identification of this life-stage. We recorded a total of 316 species and subspecies, belonging to 25 orders, 106 families and 260 genera. The ten most abundant species are composed mostly of endemic or native non-endemic species and only one exotic species (Ommatoiulus moreleti (Lucas, 1860)). They include 107 330 individuals (60%) of all sampled specimens and can be considered as the dominant species in the Azorean native forests for the target studied taxa. The Hemiptera order was the most abundant taxa, with 90 127 (50,4%) specimens. The Coleoptera order was the most diverse taxa with 30 (28,3%) family sampled. We registered 72 new species records (two for Flores, eight for Faial, 24 for Graciosa, 23 for Pico, eight for Terceira, three for São Miguel and four for Santa-Maria). None of them are new for the Azores archipelago. Most of the new records are introduced species, however abundance of such species is still low on the studied islands. This publication contributes to increase the baseline information for future long-term comparisons of the arthropods of the studied sites and the knowledge of the arthropod fauna of the native forests of the Azores, in terms of species abundance, distribution and diversity throughout seasons and years.